A new member (Camellia dakplaoensis) and new synonymization in Camellia section Piquetia (Theaceae) - Nguyen, Thi Thanh Huong; Nguyen, The Hien; Pham, Tuan Anh; Nguyen, Duc Dinh; Ngo, The Son; Luu, Hong Truong (Phytotaxa, 2025)
This study describes a new species of Camellia section Piquetia, C. dakplaoensis, from Dak Nong Province, Vietnam. Morphologically, it closely resembles C. langbianensis but differs in key floral and fruit traits, including plain yellow flowers, pedicels with 4 or 5 larger lanceolate bracteoles, adaxially glabrous sepals with a cuspidate apex, ovate to widely orbicular and adaxially glabrous petals, wholly yellow and glabrous filaments, and distinctly ridged capsules. Conservation assessments classify C. dakplaoensis as Critically Endangered (CR) under IUCN criteria. During a taxonomic re-evaluation of species within the section, C. campanulata and C. longii were proposed as heterotypic synonyms of C. cattienensis due to a lack of significant morphological distinctions and publication priority. With these findings, section Piquetia now includes 15 species, comprising eight with yellow flowers and seven with red to purple flowers.